Pengaruh Cloud Accounting dan Pengendalian Internal terhadap Kualitas Laporan Keuangan UMKM di Jawa Timur - Delpiero Siringoringo, Zefanya Ieremia; Karsam, Karsam (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2025)
This study aims to analyze the influence of cloud-based accounting technology and the strength of internal control on the quality and auditability of financial reports in micro, small, and medium enterprises in East Java. The research employed a quantitative approach using primary data collected through online questionnaires and direct interviews with 107 respondents representing micro, small, and medium enterprises. Data were analyzed with statistical software using classical assumption tests, correlation analysis, coefficient of determination, and hypothesis testing through t-test and F-test. The results indicate that the adoption of cloud-based accounting has a significant positive effect on the quality and auditability of financial reports, while internal control also has a significant positive effect on financial reporting quality. Moreover, both independent variables simultaneously provide a significant contribution to enhancing the quality and auditability of financial statements in micro, small, and medium enterprises. These findings highlight the importance of accounting digitalization and the implementation of robust internal control in strengthening transparency, accountability, and the credibility of financial reporting, thereby contributing to the advancement of accounting knowledge, particularly in the context of micro, small, and medium enterprises in Indonesia